2021
DOI: 10.1002/cssc.202100379
|View full text |Cite
|
Sign up to set email alerts
|

Cyrene™ as a Neoteric Bio‐Based Solvent for Catalyst‐Free Microwave‐Assisted Construction of Diverse Bipyridine Analogues for Heavy‐Metal Sensing

Abstract: An environment-friendly synthetic protocol was developed to access polyfunctionalized bipyridines from readily available amines, chromone-3-carboxaldehydes, and pyridinylacetonitriles under catalyst-and additive-free conditions using the biorenewable neoteric solvent dihydrolevoglucosenone (Cyrene™). In this strategy, amines served as both a mild-base promoter and a substrate. In addition, water was the only by-product of this reaction. This multi-component protocol provided highly diverse 2,3-, 3,3-, and 3,4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Under the elevated temperature conditions (150 °C), an impressive yield of 94% was obtained (entry 7, Table 7). 38 It is interesting that the authors did not observe any by-product derived from Cyrene. It was also reported that Cyrene's recovery was easily succeeded from the reaction mixture, just by removing water in vacuo .…”
Section: Cyrene In Organic Chemistrymentioning
confidence: 98%
See 3 more Smart Citations
“…Under the elevated temperature conditions (150 °C), an impressive yield of 94% was obtained (entry 7, Table 7). 38 It is interesting that the authors did not observe any by-product derived from Cyrene. It was also reported that Cyrene's recovery was easily succeeded from the reaction mixture, just by removing water in vacuo .…”
Section: Cyrene In Organic Chemistrymentioning
confidence: 98%
“…Expanding the scope of the protocol, the authors employed 3-( pyridinyl)acetonitrile and 4-( pyridine)acetonitrile, leading to the desired dipyridine analogue in good yields (72% and 64%, respectively). 38 Adhering to this logic, the authors introduced other cyano-containing molecules, such as benzyl cyanides, instead of the pyridinyl acetonitriles. Excellent results were also afforded in the presence of electron-deficient groups on the aromatic ring, whereas benzyl cyanide, as well as 4-methyl derivative, did not afford the desired product.…”
Section: Construction Of Diverse Bipyridine Analoguesmentioning
confidence: 99%
See 2 more Smart Citations
“…The dimerization reaction of sinapic ester 12 and the difluoromethylation reaction of heteroarenes or terminal alkynes 13 highlighted the beneficial use of Cyrene instead of other hazardous solvents. In many syntheses of different classes of molecules, such as isothiocyanates, 14 ureas, 15 bipyridines 16 and benzothiazoles, 17 Cyrene outperformed all other suitable solvents, offering a greener approach. Its industrial applicability was demonstrated when it was utilized in a large-scale Baylis–Hillman reaction.…”
Section: Introductionmentioning
confidence: 99%